Transitivity Analysis Annotation Scheme and Its Application to CQPweb: A Study on Stephen King’s Carrie - Amanda Hanna Astriyanti; Prihantoro Prihantoro (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2022)
In this study, I aim to create a Transitivity Analysis Annotation Scheme (TAAS) within which, process types and clause patterns are taken into account. Once created, TAAS is applied to a corpus data, obtained from a novel entitled Carrie [8]. The scheme is manually implemented using XML format. The XML formatted corpus is converted to a format accepted in CQPweb [6], a corpus query tool. The corpus is tokenised using the Perl tokenizer, in TreeTagger [10]. Once tokenised, the corpus is tagged using English TreeTagger [10], which supplies two grammatical annotations (Part of Speech and Lemma). The annotated corpus is then indexed to CQPweb. Once indexed, users are able to search the annotated corpus using transitivity analytic labels, POS tags and lemma, in CQPweb. Keywords: transitivity analysis; annotation; corpus linguistics; CQPweb